Trade And Commerce Reform During The Umayyad Dynasty - Tushofiyah, Sa'ida; Hestya Budianto, Eka Wahyu (Indonesian Journal of Islamic History and Culture, 2025)
Trade and commerce reform during the Umayyad dynasty marked a significant period in economic history, characterized by policy changes that influenced commercial activities within the caliphate. The reforms implemented by caliphs, particularly Abd al-Malik ibn Marwan, played a crucial role in stabilizing the government and enhancing trade dynamics. Previous research has explored the relationship between trade reforms and economic growth, shedding light on the interconnectedness between trade practices, economic development, and urban growth. The study of trade and commerce reform during the Umayyad dynasty presents a compelling research area with key phenomena to explore, including administrative and financial policies, trade costs, and the role of imported inputs in driving domestic growth. Understanding the mechanisms through which policy changes affected economic activities is essential for formulating effective research objectives. By setting clear research objectives to analyze the impact of policy changes on trade dynamics and economic growth, scholars can gain insights into the multifaceted nature of trade reforms during the Umayyad era. The implications of research on trade and commerce reform offer valuable lessons for understanding historical trade dynamics and their enduring impact on economic structures, contributing to a deeper understanding of economic development and governance within the Umayyad caliphate